Limited Access to Capital for SMEs and its Impact on Growth in Competitive Markets - Ermawati, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study investigates the multidimensional challenges of limited access to capital for Small and Medium Enterprises (SMEs) in competitive markets. It aims to analyze how capital constraints affect SME growth, innovation, and competitiveness while exploring the interplay of institutional, regulatory, and market factors that shape financial accessibility. Research Design and Methodology: Adopting a qualitative approach, this research utilizes a systematic literature review (SLR) to synthesize findings from recent studies. The review focuses on the structural, institutional, and operational barriers impacting SMEs’ access to finance, alongside the role of alternative financing solutions and institutional quality in mitigating these challenges. Findings and Discussion: The study identifies capital constraints as a critical barrier limiting SMEs’ ability to innovate, expand production, and compete effectively in dynamic markets. Weak institutional frameworks, such as underdeveloped credit systems and regulatory inefficiencies, exacerbate financial exclusion, particularly in developing economies. Furthermore, competitive pressures amplify these challenges, highlighting the need for alternative financing solutions like fintech and crowdfunding. However, adoption remains limited due to low financial literacy and inadequate digital infrastructure. These findings emphasize the necessity of systemic reforms to create an enabling financial ecosystem for SMEs. Implications: The study contributes to academic literature and practical applications by providing actionable insights for policymakers and financial institutions. Recommendations include simplifying credit processes, enhancing financial literacy, and fostering public-private collaborations to address systemic barriers. These strategies can empower SMEs to overcome capital constraints, drive innovation, and contribute to sustainable economic development.